1986
DOI: 10.1002/ijc.2910380207
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control study on colorectal cancer and diet in marseilles

Abstract: A case-control study of cancer of the colon and rectum was conducted in the Marseilles region of southern France. Cases (399) and a corresponding number of controls, matched for age and sex, were included, the controls being selected from patients undergoing functional re-education for injuries or trauma which reduced their mobility. A dietary history questionnaire was used to determine the usual eating habits during the year preceding diagnosis for cases, or preceding interview for controls. The cases reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(69 citation statements)
references
References 13 publications
2
65
0
2
Order By: Relevance
“…Michels et al (36) reported separate RR from two large US cohorts in their study, the Nurses' Health Study (NHS) (36a) and the Health Professionals Follow-up Study (HPFS) (36b) ; we counted the report as two prospective studies. Finally, our meta-analysis included twenty-five case-control (11,15,20,26,(28)(29)(30)(31)(33)(34)(35)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) and sixteen cohort studies (17,19,21-25,27,32,36a,36b,37,52-55) .…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Michels et al (36) reported separate RR from two large US cohorts in their study, the Nurses' Health Study (NHS) (36a) and the Health Professionals Follow-up Study (HPFS) (36b) ; we counted the report as two prospective studies. Finally, our meta-analysis included twenty-five case-control (11,15,20,26,(28)(29)(30)(31)(33)(34)(35)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) and sixteen cohort studies (17,19,21-25,27,32,36a,36b,37,52-55) .…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The items in the form included: first author's last name; year of publication; country of origin; years of study/ follow-up period; number of cases/controls; age at baseline; OR/RR and 95 % CI for the association between coffee consumption and colorectal cancer incidence, considering two exposure levels (highest v. lowest/non); type of controls; and control of confounding factors. If OR and/or 95 % CI were not reported, but numbers of cases and controls in highest v. lowest/non categories of coffee consumption were provided, these data were used to calculate crude OR and unadjusted CI (28,31,(33)(34)(35)39,40,42,46,48,49) .…”
Section: Data Extractionmentioning
confidence: 99%
“…The main carbohydrate classes studied are starch (or polysaccharides) and sugar. Epidemiological observations report a direct association between starch or polysaccharide intake and colorectal cancer although some did not achieve statistical significance (Tuyns et al, 1987;Haenszel et al, 1980;Slattery et al, 1988;Zaridze et al, 1993;Franceschi et al, 1998;Macquart-Moulin et al, 1986). However, when the end point was colorectal adenomatous polyp, a precursor of colorectal cancer, high carbohydrate intake resulted in a lower risk in both cohort (Giovannucci et al, 1992) and case -control studies (Hoff et al, 1986;MacquartMoulin et al, 1987;Benito et al, 1993;Neugut et al, 1993;Sandler et al, 1993).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Adjustments for energy intake and other possible confounders such as body weight, socio-economic status, smoking and family history of the disease were not possible in all studies. Of the seven studies that did include these adjustments (Bostick et al, 1994;Macquart-Moulin et al, 1986,1987La Vecchia et al, 1993;Centonze et al, 1994;Slattery et al, 1997), six (Bostick et al, 1994;MacquartMoulin et al, 1987;La Vecchia et al, 1993;Centonze et al, 1994;Slattery et al, 1997) found a significant increase in risk of colorectal cancer with high sugar consumption, with odd ratios (ORs) ranging from 1.4 to 2.8 for the highest quartile or quintile of intake. The picture is further complicated when food groups were analysed.…”
Section: Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation